2021
DOI: 10.3389/fgene.2021.650863
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multiomic Analysis Reveals the High-Fat Diet Induced Activation of the MAPK Signaling and Inflammation Associated Metabolic Cascades via Histone Modification in Adipose Tissues

Abstract: BackgroundThe number of diet induced obese population is increasing every year, and the incidence of type 2 diabetes is also on the rise. Histone methylation and acetylation have been shown to be associated with lipogenesis and obesity by manipulating gene expression via the formation of repression or activation domains on chromosomes.ObjectiveIn this study, we aimed to explore gene activation or repression and related biological processes by histone modification across the whole genome on a high-fat diet (HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“… 62 In adipose tissues from HFD-fed mice, integrated multiomic analysis shows that the inflammatory genes are enriched in MAPK pathways in macrophages. 68 Licochalcone F, a synthetic retrochalcone, was found to inhibit tumor necrosis factor (TNF)α-induced expression of inflammatory factors and further alleviated glucose tolerance, reduced adipocyte size, and decreased macrophage infiltration in WAT, by interacting with MAPK signaling pathway. 69 …”
Section: Signaling Pathways In the Pathogenesis Of Obesitymentioning
confidence: 99%
“… 62 In adipose tissues from HFD-fed mice, integrated multiomic analysis shows that the inflammatory genes are enriched in MAPK pathways in macrophages. 68 Licochalcone F, a synthetic retrochalcone, was found to inhibit tumor necrosis factor (TNF)α-induced expression of inflammatory factors and further alleviated glucose tolerance, reduced adipocyte size, and decreased macrophage infiltration in WAT, by interacting with MAPK signaling pathway. 69 …”
Section: Signaling Pathways In the Pathogenesis Of Obesitymentioning
confidence: 99%
“…Nowadays, there are several scientific research methods and several technologies are being developed. Some emerging research methods can be introduced into the study of adipose tissue, such as the three-dimensional genome of adipocytes and single-cell multi-omics sequencing, to discover more functional genes that play a role in the function of adipose tissue [123][124][125]. In addition, in recent years, tRNA-derived RNA fragments and piRNAs in ncRNAs have also attracted the attention of researchers [126,127], and their roles in adipose tissue are still worthy of our attention and exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications of DNAm and histone synergistically build complex epigenetic signals and alter transcriptional networks in patients with cardiometabolic disorders [ 82 ]. In a previous study, Wang et al [ 83 ] explored the effects of genome-wide histone modifications on genetic and biological processes during a high-fat diet and elucidated the relevance of gene modifications to energy metabolism and inflammation under different conditions. ChIP-seq and transcriptome in mouse adipose tissue revealed that numerous genes involved in adipogenesis, energy metabolism and inflammatory pathways were modified by H3K9me2, H3K9me3, H3K4me1 and H3K27ac histones during a high-fat diet.…”
Section: Histone Modificationmentioning
confidence: 99%